Transforming Gifted Education in Schools: Practical Applications of a Comprehensive Framework for Developing Academic Talent - Rena F. Subotnik; Paula Olszewski-Kubilius; Susan Corwith; Eric Calvert; Frank C. Worrell (MDPI AG, 2023)
The foundation for talent development as a framework for gifted education can be found in a synthesis of the psychological literature on creativity, eminence, giftedness, and high performance. The talent development framework acknowledges the contributions of both general cognitive ability and domain-specific abilities to achievement, as well as the malleability of these ability constructs. Talent development is also consistent with research on the contributions of non-cognitive or psychosocial factors to school achievement, as well as studies on factors that influence the attainment of scholarly productivity and artistry within specific domains of non-academic talent. Although there are several theoretical frameworks and models of giftedness, talent development, ability, and intelligence, each with varied areas of emphasis and desired outcomes, the research base and practical applications for the talent development megamodel (TDMM) can serve as a guide to leaders and school administrators in making fiscal and programmatic decisions that maximize short- and long-term impacts for individuals and society. In this article, we discuss some of the practical implications of the model for assessment, curriculum and instruction, and psychosocial development within a school context.